PENGEMBANGAN LKS MATERI BAHAN KIMIA DALAM KEHIDUPAN SEHARI-HARI DILENGKAPI PERMAINAN EDUKATIF SISWA KELAS VIII (Jurnal Bioconcetta, 2018)
In addition to teaching methods, the position of instructional media in the form of teaching materials in the learning process is an important part that can not be separated. But the teaching material that the author Â still found some deficiencies that led to the instructional materials less attractive to students. It is what lies behind the author to develop teaching materials in the form of worksheets on the material of chemicals in everyday life include educational games for students SMP / MTS class VIII. This study aims to produce a valid and practical worksheets for use in the learning process.This research is the development method, using a model of 4-D (four D), defining (define), design, development (develop), and disseminate. The development, researchers do the validation, which is done by three validator using the validation sheet and using sheets of questionnaire responses given to teachers and students to look at the practicalitas of the student worksheet.The results of the questionnaire validation data processing, resulting in a percentage of 96,11% were classified in the category of very valid. Test results practicalities questionnaire responses 88,8% of teachers get results and practicalities of student responses at 92,32%, which are both classified in the category of very practical.